FROM SLOVENIA TO AMERICA – THE FOOTSTEPS THROUGH TIME IN SLOVENIAN WOMEN’S AUTO/BIOGRAPHICAL BOOKS - Mirjam Milharčič-Hladnik (Dve Domovini, 2003)
The text presents some auto/biographical books, which were written by the Slovenian women immigrants to the United States or their descendants. The books deal with the immigrant experiences of women from the first and the second immigration waves. From Slovenia to America by Marie Prisland includes considerable information on Slovenian history, Slovenian communities in the United States and notable women and men, but also her autobiography. Immigrant Woman by Mary Molek is a fictionalized biography of author's mother – an immigrant woman at the beginning of the twentieth century, who led an extremely poor but nevertheless uncompromisingly principled and proud life. Irene P. Odorizzi edited a compilation of twenty one life stories, titled The Footsteps through Time. The majority of the narrators, nineteen out of twenty one, were Slovenian immigrant women who had arrived in America with the first immigration wave and they told the stories about the hardships and extremeley hard work. Mirella Besednjak described her immigrant life after the World War II in the book, Roža med trni, published recently in Slovenia. From the same period is also the immigrant experience described in the book by Josephine Janezic, Pepca’s Struggle.